Design av en kundanpassad display i wellpapp - från koncept till konstruktion - Nisén, Ylva; Yu, Emily (My University, 2026)
The purpose of this project is to explore the possibilities and limitations of corrugated cardboard and to examine how the material can be used to create an attractive display that showcases a brand. The aim is to develop and produce a display that is easy to assemble, easy to transport, and through its design promotes the hypothetical client Red Bull, a brand heavily associated with strength, endurance, and extreme sports. A preliminary study was undertaken to determine how corrugated cardboard displays are used today, how they are structurally built, and what material properties need to be considered. This was done through literature studies, observational studies, and unstructured interviews. An early ideation using brainwriting, brainstorming, sketches, and the KJ Method was conducted to establish a collaborative vision. Findings revealed that corrugated cardboard is a beneficial alternative from an environmental standpoint, as it has a high recycling rate, is lightweight, and can be designed compactly for transportation. However, corrugated fiberboard can be either rigid or bendable depending on the direction of its wave pattern. Compromises in the design are therefore often necessary to make the product more structurally stable and user-friendly. Computer-aided design, prototypes, and sketches were central to the process, enabling a clearer understanding of how two-dimensional drawings translate into physical products. The final product, a Formula 1- and Soapbox Race-inspired Point-of-Sale display, was fabricated to validate these findings. The result reveals that it is possible to design an attractive corrugated cardboard display that, through a strong visual expression, showcases and strengthens a brand’s identity.
Keywords: Point-of-Sale display; corrugated cardboard; construction; brand identity; design for assembly